Spatial Analysis of Public Green Open Space Availability Based on Area and Population in Tapin Utara Sub-District - Virgiawan, Doni; Adyatma, Sidharta; Saputra, Aswin Nur; Rahman, Akhmad Munaya; Ibrahim, Mohd Hairy bin (Sustainability (STPP) Theory, Practice and Policy, 2025)
This study aims to assess the availability of public green open spaces (GOS) in North Tapin District and to calculate the required GOS based on current population size, land area, and projected demographic growth up to the year 2044. Employing a quantitative descriptive methodology, the research utilizes Geographic Information System (GIS) spatial analysis complemented by field observations and ground truthing to ensure data accuracy. The study area includes all public green open spaces within the district boundaries. Results reveal that the total public GOS area is approximately 35.82 hectares, representing 5.48% of the district’s total land area—substantially below the minimum regulatory standard of 20%. Population projections indicate a future GOS demand of 72.16 hectares by 2044, highlighting a significant shortfall in current provision. These findings demonstrate that North Tapin District’s existing green open spaces are insufficient to meet both present and anticipated needs, underscoring the urgent requirement for strategic urban planning interventions to expand and optimize green space allocation.